2000
DOI: 10.1177/014920630002600308
|View full text |Cite
|
Sign up to set email alerts
|

Applicants’ Perceptions of Selection Procedures and Decisions: A Critical Review and Agenda for the Future

Abstract: This review critically examines the literature from 1985 to 1999 on applicant perceptions of selection procedures. We organize our review around several key questions: What perceptions have been studied? What are determinants of perceptions? What are the consequences or outcomes associated with perceptions applicants hold? What theoretical frameworks are most useful in examining these perceptions? For each of these questions, we provide suggestions for key research directions. We conclude with a discussion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
526
1
5

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 380 publications
(539 citation statements)
references
References 90 publications
7
526
1
5
Order By: Relevance
“…This work should examine actual applicants whenever possible. Future work should also build on those studies that have examined applicant withdrawal (e.g., Ryan et al, 2000;Truxillo et al, 2002). Organizations that are concerned with applicant retention and, more specifically, losing top applicants (Murphy, 1986), should track how reactions compete with other factors to explain self-selection from the hiring process.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…This work should examine actual applicants whenever possible. Future work should also build on those studies that have examined applicant withdrawal (e.g., Ryan et al, 2000;Truxillo et al, 2002). Organizations that are concerned with applicant retention and, more specifically, losing top applicants (Murphy, 1986), should track how reactions compete with other factors to explain self-selection from the hiring process.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…Finally, and perhaps most importantly, recent research has shown that outcome favorability (Ryan & Ployhart, 2000) and perceived performance (Chan, Schmitt, Jennings, Clause, & Delbridge, 1998a) are key determinates of justice judgments and post-test motivation, suggesting that self-serving bias is a critical mechanism in the formation of many applicant reactions. The current study continues this vein of research by examining the effects of both expected outcome and actual outcome on justice judgments and test-taking motivation.…”
Section: Self-serving Biasmentioning
confidence: 99%
“…In their review of applicant reactions research, Ryan and Ployhart (2000) cite a wide array of studies that show outcome favorability as a primary determinant of applicant reactions. In other words, applicants who do not receive the job generally perceive the selection process as less fair than those who do receive the job.…”
Section: Self-serving Biasmentioning
confidence: 99%
See 2 more Smart Citations